ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KONEKSI POLITIK DAN LEVERAGE TERHADAP TAX AVOIDANCE - Septiana, BRENDA SEPTIANA B1031161075 (Jurnal KIAFE, 2020)
Abstract This study aims to examine and provide empirical evidence regarding the effect of corporate social responsibility(CSR), political connections, and leverage on tax avoidance. This research was conducted the mining companies listed on the Indonesia Stock Exchange in 2016-2018. The data was processed using Eviews 10 program to obtain a comprehensive picture of the relationship between one variable with another variable. The sample in this study consisted of 14 companies for 3 years from 2011-2015 with purposive sampling as a sampling method. The results of this study indicate that political connections have a significant positive effect on tax avoidance, while corporate social responsibility and leverage have no effect because they are not significant to tax avoidance. Keywords: Corporate Social Responsibility(CSR), Political Connections, Leverage, Tax AvoidanceDAFTAR PUSTAKA Andhari, P. A. S., & Sukartha, I. M. (2017) Pengaruh Pengungkapan Corporate Social Responsibility, Profitabilitasm Inventory Intensity, Capital Intensity dan Leverage Pada Agretivitas Pajak. E-Jurnal Akuntansi Universitas Udayana, 18 (3), 2115-2142.Anindyka, D., Pratomo. D., Kurnia (2018) Pengaruh Leverage (DAR), Capital Intensity dan Inventory Intensity terhadap Tax Avoidance. E-Proceeding of Management: Vol.5, No 1.Butje, S., & Tjondro, E. (2014) Pengaruh Karakteristik Eksekutif dan Koneksi Politik terhadap Tax Avoidance. Tax & Accounting Review, Vol 4, No 2.Cheers, Zachar. 2011. The Corporate Social Responsibility Debate. Spring.Danang Sugianto (2019) Mengenal Soal Penghindaran Pajak yang Dituduhkan ke Adaro (2019) Diakses pada 2019 dari http://m.detik.com/finance/berita-ekonomi-bisnis/d-46112708/mengenal-soal-penghindaran-pajak-yang-dituduhkan-ke-adaro.Darmayanti, P. P. B., & Merkusiwati, N. K. L. A. (2019) Pengaruh Ukuran Perusahaan, Profitabilitas, Koneksi Politik dan Pengungkapan Corporate Social Responsibility Pada Tax Avoidance. E-Jurnal Akuntansi Universitas Udayana, 26 (3), 1992-2019.Darwin, A., 2010, Penerapan Sustainability Reporting di Indonesia. Konvensi Nasional Akuntansi V, Program Profesi Lanjutan. Yogjakarta, 13-15 Desember.Deegan, C., Rankin, M. and Tobin, J. (2002), “An Examination of the Corporate Social and Environmental Disclosures of BHP from 1983-1997: A Test of Legitimacy Theory”, Accounting, Auditing and Accountability Journal, Vol 15, No 3, pp. 312-43.Dharma, N. B. S., & Noviari, N. (2017) Pengaruh Corporate Social Responsibility dan Capital Intensity Terhadap Tax Avoidance. E-Jurnal Akuntansi Universitas Udayana, 18(1), 529-556.Faccio, M. (2006). Politically Connected Firms. The American Economic Review, 369-386.Fassin, Yves. 2009. “The Stakeholder Model Refined”. Journal of Business Ethics, D/7012/13. Freeman, R. E. 1984. Stategic Management: A Stakeholder Approach, Boston, Pitman.Fisman, R. 2001. Estimating the Value of Political Connections. American Economic Review 91: 1095-1102.Ghozali, I. 2013. Aplikasi Analisis Multivariate dengan Program IBM SPSS 21 Edisi 7, Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I., & Ratmono, D. (2013) Analisis Multivariat dan Ekonometrika Teori, Konsep, dan Aplikasi dengan Eviews 10. Semarang: Badan Penerbit Universitas Diponogoro.Gray, R., Kouhy, R., dan Lavers, S. 1995. “Corporate Social and Environmental Reporting: A Review of Literature and a Longitudinal Study of UK Disclosure”, Accounting, Auditing and Accountability Journal, vol, 8, No. 2, pp. 47-76.Gray, et al. (1996). Accounting and Accountability: Changes and Challenges in Corporate Social and Environmental Reporting. Prentice Hall Europe, Hemel Hempstead.Gujarati, Damodar N, (2009). Basic Econometrics, Fourth edition, Singapore. McGraw-Hill Inc.Hadi, Noor. 2011. Corporate Social Responsibility. Yogyakarta: Graha IlmuHifnalisa, K. (2019) Pengaruh Pengungkapan Corporate Social Responsibility, Capital Intensity, Koneksi Politik, dan Corporate Risk Terhadap Penghindaran Pajak (Skripsi), Universitas Pasundan Bandung, Indonesia.Hidayat, K., Ompusunggu, A. P., & Suratno, H. (2016) Pengaruh Corporate Social Responsibility terhadap Agresivitas Pajak dengan Insentif Pajak Sebagai Pemoderasi. Jurnal Ilmiah Akuntansi Fakultas Ekonomi. 2(2), 39-58.Homle, L., Watts, P., 2006. Human Rights and Corporate Social Responsibility. World Business Council for Sustainable Development, Geneva.Hutami, Sri. Tax Planning (Tax Avoidance dan Tax Evasion) Dilihat Dari Teori Etika. Jensen, M. and Meckling, W. (1976): “Theory of the firm: managerial behavior, agency costs and ownership structure”, Journal of Financial Economics 3, 305-360.John Elkington. (1997). Cannibals with Forks : The Tripple Botton Line of 21st Centaury Business. Oxford. UK : Capstone.Kasmir. 2013. Analisis Laporan Keuangan. Rajawali Pers : JakartaKessler, J (2004) “Tax Avoidance Purpose and Section 741 of taxes Act 1988”. British Tax Review.Kim, C. F., & Zhang, L. (2014). Corporate Political Connections And Tax Aggressiveness. Contemporary Accounting Research, Forthcoming.Lako, Andreas (2011). Dekonstruksi CSR dan Reformasi Paradigma Bisnis dan Akuntansi. Jakarta. Erlangga.Lanis, R., & Richardson, G. (2007). Determinants of the Variability in Corporate effective Tax Rates and Tax Reform: Evidence form Australia. Journal of Accounting and Public Policy. 26 (2007) 689-704. Lanis, R., & Richardson, G. (2011). The Effect of Board of Director Composition on Corporate Tax Aggressiveness. Journal of Accounting and Public Policy, 30 (2011), 50-70.Lanis, R., & Richardson, G. (2012). Corporate social responsibility and tax aggressiveness: a test of legitimacy theory. Accounting, Auditing & Accountability Journal, 26 (1), 75-100.Lanis, R., & Richardson, G. (2012). Corporate social responsibility and tax aggressiveness: An enpirical analysis. J. Account. Public Policy 31. 86-108Leuz, C., & Oberholzer-Gee, F. (2006). Political Relationships, Global Financing, And Corporate Transparency: Evidence From Indonesia. Journal Of Financial Economics, 81(2), 411-439.Levin, R.I., dan Rubin, D.S. (1998), Statistics for Management, 7th edition.Mulyani, S. (2014). Pengaruh Karakteristik Perusahaan, Koneksi Politik Dan Reformasi Perpajakan Terhadap Penghindaran Pajak (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Tahun 2008-2012). Jurnal Mahasiswa Perpajakan, 1(2).Murniyana, W G. 2018. “Pengaruh Koneksi Politik, Harga Transfer, Leverage dan Pertumbuhan Penjualan Terhadap Penghindaran pajak”. Fakultas Ekonomi Universitas IslamIndonesia Yogyakarta.Napitu, A. T., & Kurniawan, C. H. (2016). Analisis Faktor-Faktor yang Mempengaruhi Agresivitas Pajak Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2012-2014. Simposium Nasional Akuntansi XIX Lampung, 2016.Nugraha, N.B. & Meiranti, W. (2015). Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Profitabilitas, Leverage, dan Capital Intensity Terhadap Agresivitas Pajak. Diponegoro Journal of Accounting, 4 (4), 1-14.Nugraha, N. B. (2015). Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Profitabilitas, Leverage dan Capital Intensity terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di BEI Selama Periode 2012-2013 (Skripsi Publikasi), Universitas Diponegoro, Indonesia.Pradnyadari, I. D. A. I., & Rohman, A. (2015). Pengaruh Pengungkapan Corporate Social Responsibility terhadap Agresivitas Pajak. Diponegoro Journal Of Accounting, 4(2), 2337-3806.Pranoto, B. A., & Widagdo, A. K. (2015). Pengaruh Koneksi Politik dan Corporate Governance terhadap Tax Aggressiveness. Syariah Paper Accounting FEB UMS (hlm. 472-486). Surakarta, Indonesia: Universitas Negeri Sebelas Maret.Purwanti, S. M dan Sugiyarti, L (2017) Pengaruh Instensitas Aset Tetap, Pertumbuhan Penjualan dan Koneksi Politik terhadap Tax Avoidance. Jurnal Riset Akuntansi dan Keuangan 5(3), 2017, 117-134.Puspitasari, N. dan C. (2014). Pengaruh Leverage, Kepemilikan Institusional, dan Ukuran Perusahaan Terhadap Penghindaran Pajak (Tax Avoidance) Pada Perusahaan Sektor Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2010-2012, XVIII(3), 408–421Sarwono, Jonathan. 2016. “Prosedur-Prosedur Analisis Populer Aplikasi Riset Skripsi dan Tesis dengan Eviews”. Yogjakarta: Gava Media.Scott, William R. (2000). Financial Accounting Theory. Second Edition Canada: Prentice Hall.Suchman, Mark, C., 1995. “Managing Legitimacy: Strategies and Institutional Approach, Academy of Management Review”, 20(3). 571-610.Syamsudin. (2004). Managemen Keuangan Perusahaan. Jakarta: PT. Raja Grafindo Persada.Taylor & Ho. (2007). An Empirical Analysis of Triple Bottom-Line Reporting and its Determinants: Evidence from the United States and Japan. Watson, Luke, 2011. “Corporate Social Responsibility and Tax Aggressiveness: An Examination of Unrecognized Tax Benefits”. Social Science Research NetworkWibisono, Yusuf. 2007. Membedah Konsep & Aplikasi CSR. Gresik: Fascho PublishingYanti, M. G. (2019). Analisis Pengaruh Corporate Social Responsibility, Komisaris Independen, dan Komite Audit Terhadap Agresivitas Pajak (Skripsi), Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, Indonesia.Yoehana, M. (2013). Analisis Pengaruh Corporate Social Responsibility terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2011 (Skripsi Publikasi), Universitas Diponegoro, Indonesia.Yulfaida dan Zhulaikha, 2012. Pengaruh Size, Proftabilitas, profile, Leverage Dan Ukuran Dewan Komisaris Terhadap Pengungkapan Tanggung Jawab Sosial Pada Perusahaan Manufaktur di Bursa Efek Indonesia, Semarang: UNDIP, Diponogoro Journal Of Accounting Volume 1, Nomor 2, Tahun 2012, Halaman 1-12.Zain, M. (2008). Manajemen Perpajakan (ed.3). Jakarta: Salemba Empat.Zhang, H., Li, W., Jian, M. 2012. How Does State Ownership Affect Tax Avoidance? Evidence from China. Workingpaper. School of Accountancy, Singapore Management University.Peraturan Perundang- Undangan Undang-Undang Nomor 36 Tahun 2008 pasal 17 ayat 2a mengatur ketetapan tarif pajak penghasilan.Undang-Undang RI No. 40 Tahun 2007 pasal 74 tentang tanggung jawab sosial dan lingkungan bagi perusahaan.UU No. 36 Tahun 2008 tentang Pajak PenghasilanUndang-Undang Nomor 28 Tahun 2007 Tentang Ketentuan Umum dan Tata Cara Perpajakan (KUP)Undang- Undang Nomor 16 Tahun 2009 Tentang Ketentuan Umum dan Tata Cara Perpajakan.WebsiteGlobal Reporting Initiative (GRI). 2013. Sustainability Reporting Guidelines (versi GRI–G4 Bahasa Indonesia). http://www.globalreporting.orghttp://m.detik.com/finance/berita-ekonomi-bisnis/d-4612708/mengenal-soal-penghindaran-pajak-yang-dituduh-ke-adaro.http://m.hukumonline.com/klinik/detail/ulasan/it5c468d7988077/kewajiban-perusahaan-tambang-melaksanakan-csr.http://pajak.co.id/id/artikel/praktik-penghindaran-pajak-di-indonesiahttp://www.hestanto.web.id/penghindaran-pajak/https://www.idx.co.id/.https://www.sahamok.com/.Laporan kinerja Direktorat Jenderal Pajak (2018). http://www.pajak.go.id